Islamic Insurance: A Potential Niche Market of Indonesia - Effendi, Jaenal (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
Islamic insurance in Indonesia is potentially expected to grow along with the increase in Islamic financial market. Hence, this paper aims to develop strategy and policy recommendations for stakeholders of Islamic insurance industry in Indonesia. This article applied ANP approach by classifying it into three aspects, namely problem, solution, and strategy. Problem and solution aspects consist of four clusters including internal, customer, competition, as well as regulation. Also, strategy offered is the strategy to improve the quality of service, strategy to develop the relationship and synergy between the authorities and the Islamic Financial Institutions. DOI: 10.15408/aiq.v10i1.5330